Carrières criminelles collectives : évolution d’une population délinquante (groupes de motards) - Tremblay, Pierre; Laisne, Sylvie; Cordeau, Gilbert; Shewshuck, Angela; MacLean, Brian (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
Co-offending has not been a major area of research for students of crime careers. This paper, however, offers a preliminary analysis of an extensive set of intelligence files gathered by law enforcement agencies on biker groups over a 14 year period (1974-1988). Data has been collected on size, location, network status, life span and degree of crime involvement of 62 criminally involved adult biker groups having operated in Eastern Canada (Quebec) during that period. Findings show a substantial drop in participating groups. Further, remaining groups have not become larger as shown by the equally substantial drop in the overall core underworld biker population. Alternative explanatory accounts for this overall drop are considered.